Popularity is Everything: A new approach to protecting passwords from statistical-guessing attacks - Schechter, Stuart; Herley, Cormac; Mitzenmacher, Michael (The 5th USENIX Workshop on Hot Topics in Security (HotSec '10), 2010)
We propose to strengthen user-selected passwords against statistical-guessing attacks by allowing users of Internet-scale systems to choose any password they want-so long as it's not already too popular with other users. We create an oracle to identify undesirably popular passwords using an existing data structure known as a count-min sketch, which we populate with existing users' passwords and update with each new user password. Unlike most applications of probabilistic data structures, which seek to achieve only a maximum acceptable rate false-positives, we set a minimum acceptable false-positive rate to confound attackers who might query the oracle or even obtain a copy of it.
This paper scheduled to be made public 12:01AM, July 19.